Ograniczenie prawa do udziału w postępowaniu administracyjnym podmiotów trzeciego sektora - Mrożek, Jakub (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2017)
This article discusses the limitation of the right of third sector entities to participate in the recruitment procedure for first class public primary schools. This includes the legal analysis of the above procedure in compiling it with the provisions of the Code of Administrative Procedure. It explains the essence of the restriction in question, and also defines its scope. At the same time - because the described restrictions, in the scope of the ability of the activities of entities of the III sector, influence closely related to the above proceedings court proceedings in the case of recruitment to these schools - the article also describes the limitations that the entities of the III sector of such cases. It was indicated that these limitations are the result of the obstructions that arise in the course of proceedings before the recruitment commission and the head of the public primary school. In addition, they define the scope of these restrictions, while pointing out the plane on which entities of the III sector can operate without interruption.
Keywords: administrative court; education; sector iii entity; first class; directors; recruitment; primary schools; decision; public school